2006
DOI: 10.1007/s00213-006-0378-3
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of contrast sensitivity in long-term lorazepam users

Abstract: The results are discussed in terms of their possible impact on everyday life. As visual acuity does not allow the detection of the impairments that are observed in the present study, it is suggested that a more systematic exploration of contrast sensitivity be carried out in long-term users of benzodiazepines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Furthermore, pharmacological medication [18] and alcohol abuse [16] can cause reduced contrast sensitivity. Older persons who are long-term users of benzodiazepines have perceptible impairment of contrast sensitivity [14]. The moderate coefficients of determination R 2 of the regression of CS and scatter with age indicates that only a small part of the variance of CS and scatter, respectively, is described by the influence of age.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pharmacological medication [18] and alcohol abuse [16] can cause reduced contrast sensitivity. Older persons who are long-term users of benzodiazepines have perceptible impairment of contrast sensitivity [14]. The moderate coefficients of determination R 2 of the regression of CS and scatter with age indicates that only a small part of the variance of CS and scatter, respectively, is described by the influence of age.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that several reviewed studies had shown a global loss of contrast sensitivity with benzodiazepines. [124,125] Furthermore, this trial's specific findings were that long-term lorazepam recipients exhibited impaired contrast Continued next page sensitivity (and exophoria), and this was independent of the sedative effects of the benzodiazepine. This was seen to be concomitant with a normal visual acuity.…”
Section: Benzodiazepinesmentioning
confidence: 95%
“…In a recent study published in 2006, Giersch et al [124] reviewed the literature concerning the effects of benzodiazepines (both in acute or longterm usage) on visual acuity and especially on contrast sensitivity. In addition, the researchers ophthalmologically tested 15 long-term lorazepam recipients and 15 matched untreated healthy subjects.…”
Section: Benzodiazepinesmentioning
confidence: 98%
“…As a result, the use of benzodiazepine was determined to have a global loss on contrast sensitivity. 76,77 Furthermore, the rise of development of contrast sensitivity and exophoria in patients using long term lorazepam is found to be free of sedative efficiency of benzodizapines. Visual acuity has remained normal on these patients.…”
Section: Benzodiazepinesmentioning
confidence: 97%
“…76 have made literature review on visual acuity of benzodiapines on acute or chronic basis and the effect on contrast sensitivity. In addition, 15 patients who had a long term treatment of lorazepam were compared to healthy control group.…”
Section: Benzodiazepinesmentioning
confidence: 99%